Interactive effects of cold and temperate conditions on growth and biochemical content of Antarctic microalga Chlorella variabilis YTU.ANTARCTIC.001 - Inan, Benan; Akin, Basak; Unlue, Ilayda Dilara; Kocer, Anil Tevfik; celik, Arzu; Vehapi, Meyrem; Kaya, Yilmaz; Ozcimen, Didem (SPRINGER, 2023)
The aim of this study was to isolate and identify Antarctica microalgae collected through the National Antarctic Science Expedition and to examine the growth responses and biochemical contents of Chlorella variabilis under cold and temperate cultivation conditions in growth medium consisting of various nitrogen concentrations under different lighting cycle parameters. In this study, the Antarctic microalgae Chlorella variabilis YTU.ANTARCTIC.001, was cultivated at different temperatures of 4, 13, 20 and 27 degrees C in modified BG-11 medium with various concentrations of NaNO3 (0, 0.75, 1.5, 2.5 and 3 g L-1) under three photoperiods (8:16, 16:8 and 24:0) to investigate the growth and biochemical compositions. The specific growth rate changed from 0.012 to 0.23 day(-1) with an increase in nitrate concentration, temperature and light cycle. The highest specific growth rate was 0.23 day(-1) using the growth medium that consisted of 3 g L-1 nitrate at 27 degrees C under 16:8 h light-dark cycle, while there was no algal growth at 4 degrees C. Carbohydrate, protein, chlorophyll-a and beta-carotene contents of microalgae increased with the increasing concentrations of nitrogen at 20 degrees C and 27 degrees C. The highest lipid content was achieved as 66% DW, using the growth medium consisting of 0.75 g L-1 nitrate at 13 degrees C. This study highlighted that the production of the Antarctic microalgae C. variabilis can be carried out efficiently in temperate conditions by manipulating the growth parameters.
Keywords: Antarctic microalgae; Chlorophyta; Psychotrophic microorganism; Stress cultivation; Physiological changes; FATTY-ACID-COMPOSITION; FRESH-WATER MICROALGA; LIGHT; PHOTOSYNTHESIS; EXTREME; ENVIRONMENTS; INFLAMMATION; EXTRACTION; VULGARIS; BIOMASS; Biotechnology & Applied Microbiology; Marine & Freshwater Biology